Dysregulated flow‐mediated vasodilatation in the human placenta in fetal growth restriction. (8th June 2015) - Jones, Sarah; Bischof, Helen; Lang, Ingrid; Desoye, Gernot; Greenwood, Sue L.; Johnstone, Edward D.; Wareing, Mark; Sibley, Colin P.; Brownbill, Paul
Abstract : Key points: A correlation was found between in vivo umbilical artery Doppler velocimetry and resistance to fetal‐side flow in the human ex vivo dually perfused placenta, highlighting that the fetoplacental vascular bed is a key site of resistance to umbilico‐placental flow in pregnancy. We discovered high resistance and poor flow‐mediated vasodilatory responses in placentas from pregnancies associated with fetal growth restriction (FGR). Endothelial cells isolated from the FGR placentas and grown in static and flow culture showed a dysregulated phenotype, with biochemical signalling demonstrating a failed compensatory response to high blood‐flow resistance. Abstract: Increased vascular resistance and reduced fetoplacental blood flow are putative aetiologies in the pathogenesis of fetal growth restriction (FGR); however, the regulating sites and mechanisms remain unclear. We hypothesised that placental vessels dictate fetoplacental resistance and in FGR exhibit endothelial dysfunction and reduced flow‐mediated vasodilatation (FMVD). Resistance was measured in normal pregnancies ( n  = 10) and FGR ( n  = 10) both in vivo by umbilical artery Doppler velocimetry and ex vivo by dual placental perfusion. Ex vivo FMVD is the reduction in fetal‐side inflow hydrostatic pressure (FIHP) following increased flow rate. Results demonstrated a significant correlation between vascular resistance measured in vivo and ex vivo in normal pregnancy, but not in FGR. In perfused FGR placentas, vascular resistance was significantly elevated compared to normal placentas (58 ± 7.7 mmHg and 36.8 ± 4.5 mmHg, respectively; 8 ml min −1 ; means ± SEM; P  < 0.0001) and FMVD was severely reduced (3.9 ± 1.3% and 9.1 ± 1.2%, respectively). In normal pregnancies only, the highest level of ex vivo FMVD was associated with the lowest in vivo resistance. Inhibition of NO synthesis during perfusion (100 μm l ‐NNA) moderately elevated FIHP in the normal group, but substantially in the FGR group. Human placenta artery endothelial cells from FGR groups exhibited increased shear stress‐induced NO generation, iNOS expression and eNOS expression compared with normal groups. In conclusion, fetoplacental resistance is determined by placental vessels, and is increased in FGR. The latter also exhibit reduced FMVD, but with a partial compensatory increased NO generation capacity. The data support our hypothesis, which highlights the importance of FMVD regulation in normal and dysfunctional placentation.